Estimating the effects of tourism growth on emission pollutants: empirical evidence from a small island, Cyprus - Katircioglu, Setareh; Saqib, Najia; Katircioglu, Salih; Kilinc, Ceyhun C.; Gul, Hasan (Springer, 2020)
This study searches the impact of tourism growth on emission pollutants in Cyprus (north), which is a small island in the Mediterranean and has shown significant development in hotel and casino sectors in the last two decades. Results from time-series analyses reveal that an inverted U-shaped EKC hypothesis is confirmed for Cyprus with and without tourism development. Tourism also exerts positively significant and long-term effects on the levels of carbon emissions, revealing that growth in the tourism sector causes degradation in the environment.
Keywords: Tourism; EKC; Energy consumption; Small island; Cyprus